Answer:
(u o w) (7) = 22
(w o u) 7) = 8
Explanation:
We are given:
![u(x)= x^2+6\\w(x)= √(x+9)](https://img.qammunity.org/2022/formulas/mathematics/college/z3z4ei48udcoy4v8j9lopq0t0vh89mcusi.png)
We need to find:
a) (u o w) (7)
First we will find (u o w) (x) and then we will find (u o w) (7)
We know that (u o w) (x) = u(w(x))
Put value of w(x) into u(x)
we have:
![u(x)=x^2+6\\Put\: x =√(x+9)\\u(w(x))=(√(x+9))^2+6\\u(w(x))=x+9+6\\ u(w(x))=x+15](https://img.qammunity.org/2022/formulas/mathematics/college/5l3k18mrx9naksre93fjdu6bl845ilj1fz.png)
Now finding (u o w) (7)
We know that: (u o w) (7) = u(w(7))
![u(w(x))=x+15\\Put\:x=7\\u(w(7))=7+15\\u(w(7))=22](https://img.qammunity.org/2022/formulas/mathematics/college/kinyy1c7ljuvs74qmogucnwjoe2q5rkudz.png)
So, (u o w) (7) = 22
b) (w o u) (7)
First we will find (w o u) (x) and then we will find (w o u) (7)
We know that (w o u) (x) = w(u(x))
Put value of u(x) into w(x)
we have:
![w(x)= √(x+9)\\Put\:x=x^2+6\\w(u(x))= √((x^2+6)+9)\\w(u(x))= √(x^2+6+9)\\w(u(x))= √(x^2+15)](https://img.qammunity.org/2022/formulas/mathematics/college/iwfntnrf6norsnq5r2c6cir7wzcjk4dt6j.png)
Now finding (w o u) (7)
We know that (w o u) (7) = w(u(7))
![w(u(x))= √(x^2+15)\\Put\:x=7\\w(u(7))= √((7)^2+15)\\w(u(7))= √(49+15)\\w(u(7))= √(64)\\w(u(7))= 8](https://img.qammunity.org/2022/formulas/mathematics/college/w9ej0chsdx88t1mpz4j79vkjtipz923ht9.png)
So, (w o u) (7) = 8